PENGARUH PAY SATISFACTION, BENEFIT SATISFACTION, OCCUPATIONAL STRESS TERHADAP TRUNOVER INTENTION YANG DIMEDIASI OLEH ORGANIZATIONAL COMMITMENT PADA KARYAWAN RUMAH SAKIT - Meydiana Eka Rahayu; Tiara Puspa (STMIK Widuri Jakarta, 2025)
The present study aims to analyse the effect of pay satisfaction, benefits satisfaction, and occupational stress on hospital employees' turnover intention, with organisational commitment as the mediating variable. The study's background is rooted in the significance of employee retention in enhancing productivity and organisational sustainability. It also acknowledges the paucity of research that has concurrently examined the internal and external factors that influence turnover intention. The present study employs a conceptual framework that integrates the theories of job satisfaction, job stress, organisational commitment, and turnover theory. The results of the literature review demonstrate that satisfaction with salary and benefits is associated with increased organisational commitment and decreased turnover intention, while job stress is associated with decreased commitment and increased turnover intention. Organisational commitment has been demonstrated to play a significant mediating role in the relationship between salary satisfaction, benefits, job stress, and turnover intention. The findings of this study are expected to assist hospital organisations in the design of effective retention strategies by paying attention to aspects of compensation, benefits, the management of work stress, and the strengthening of organisational commitment, with a view to reducing turnover rates and increasing employee loyalty.